Ta có: \(2n-3⋮n+1\)
\(\Leftrightarrow2n+2-5⋮n+1\)
\(\Leftrightarrow2.\left(n+1\right)-5⋮n+1\)
mà \(2.\left(n+1\right)⋮n+1\)
\(\Rightarrow5⋮n+1\)
\(\Rightarrow n+1\inƯ\left(5\right)=\left\{\pm1;\pm5\right\}\)
Tìm nốt x nhé.
Theo đề bài : 2n - 3 chia hết cho n + 1
=> 2n -3 - (n + 1) chia hết cho n + 1
=> 2n - 3 - 2(n+1) chia hết cho n + 1
=> 2n - 3 - 2n - 2 chia hết cho n + 1
=> 1 chia hết cho n + 1
=> n + 1 = { 1 ; -1}
=> n = { 0 ; -2 }
Vì n thuộc Z*
=> n = -2
Vậy n = -2
Nguyễn Thảo Nguyên
2n-3-2n-2 =-5 nhé bạn
\(2n-3⋮n-1\)
\(2.\left(n-1\right)-1⋮n-1\)
\(1⋮n-1\)
Lập bảng